Brain Lesion Segmentation Using Fuzzy C-Means On Diffusion-Weighted Imaging - Fateeha Muda, Ayuni; Mohd Saad, Norhashimah; Syed Abu Bakar, Syed Abdul Rahman; Muda, Sobri; Abdullah, Abdul Rahim (Asian Research Publishing Network (ARPN), 2015)
-